Deteksi Kerusakan Pipa Dalam Bentuk Kebocoran Menggunakan Sinyal Suara Dan Dual Mikrofon - Hariadi Hariadi; Feblil Huda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The piping system is an important feature in the industrial world because it has an effective and efficient transportation function used for shipping such as liquid and gas fluids. Prevention of damage either leakage or blockage is very important because it can reduce the number of losses both economic, natural environment, and even loss of life. The use of sound signals to detect and find leaks in pipes with experimental studies. This method can be used because it is very sensitive to discontinuities in the pipe that can detect damage at a relatively lower cost. This method uses sound impulses emitted through the loudspeaker as excitation and the response of the sound signal will be recorded using a dual microphone sensor. Sound signals are given for leakage under conditions of using water and without water of different sizes, positions and polar sides. The sound signal data will be processed using the Fast Fourier Transform and Wavelet Transform methods. The test results showed that the amount of damage given is directly proportional to the amplitude generated and the wavelet coefficient of each microphone sensor will increase as it approaches the polar side of the damage. Keywords : Sound Signal, Leakage, Fast Fourier Transform, Wavelet Transform, Dual Microphone